Sweat Park Sport Centre / Nina Syazwani Sarif ... [et al.] - Sarif, Nina Syazwani; Anual, Nurulakmar; Shahidan, Shazerina Maliani; Zulkepli, Siti Nur Ain (Faculty of Communication and Media Studies, 2005)
Interest in involving in business world has made four of the partners to get involved and took the opportunity by providing Service of the sports center calied 'Sweat Park'. The govemment has implemented many policies for Bumiputra entrepreneurs in order to encourage competition among each other. Similar to that policy, four of us has decide to Starts this sports center.